1995
DOI: 10.1089/aid.1995.11.1169
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Syncytium-Inducing Phenotype of HIV Type 1 Is Associated with Positively Charged Residues in the HIV Type 1 gp120 V2 Domain without Fixed Positions, Elongation, or RelocatedN-Linked Glycosylation Sites

Abstract: The prevalence of HIV-1 sequences of the envelope domains V1V2 and V3 was analyzed by RT-PCR amplification. Two distinct biological phenotypes of HIV-1 have been described: the nonsyncytium-inducing (NSI) phenotype, best characterized by the inability to infect MT-2 cells, and the syncytium-inducing phenotype (SI), with the ability to infect MT-2 cells. Viral phenotype SI has been associated with HIV pathogenesis. The presence of positively charged amino acids at position 306 and 320 in the V3 domain of gp120 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 14 publications
3
21
1
Order By: Relevance
“…The changes in the surface electrostatic potential, resulting from immunological pressure, could affect the manner by which NoVs interact with the cell surface receptors through avidity effects. The modulation of cell binding due to alterations of the surface charge was noted previously in the cases of influenza virus (14) and HIV (8). This may explain the results of elegant surrogate HBGA blockade assays, used in lieu of neutralization assays, that showed different binding activities of pre-and postepidemic antisera (23).…”
Section: Discussionsupporting
confidence: 53%
“…The changes in the surface electrostatic potential, resulting from immunological pressure, could affect the manner by which NoVs interact with the cell surface receptors through avidity effects. The modulation of cell binding due to alterations of the surface charge was noted previously in the cases of influenza virus (14) and HIV (8). This may explain the results of elegant surrogate HBGA blockade assays, used in lieu of neutralization assays, that showed different binding activities of pre-and postepidemic antisera (23).…”
Section: Discussionsupporting
confidence: 53%
“…Overall, amino acid changes throughout the region have been shown to be important in terms of structure, function and antibody-mediated neutralisation . More recently it has been demonstrated that SI isolates carry more positive charge in V2 compared to NSI isolates (Cornelissen et al, 1995) and that the V1-V2 region can de®ne both tropism and cytopathicity independently of the V3 sequence (Palmer et al, 1996). For the prototype strain HIV-1HXB2, removal of a glycosylation site (213 to 215; Figure 3) results in a non-viable virus and length differences in V2 modulate exposure of the CD4-binding site and the immunoreactivity of SU (Fox et al, 1997).…”
Section: V1-v2mentioning
confidence: 99%
“…Previously published data on the role of the V3 loop in the formation of syncytia, as well as its role in the determination of tropism in strains of HIV-1, suggested that the dominant effect of the V3 loop was, in fact, on cellular tropism (Harrowe & Cheng-Meyer, 1995 ;Cann et al, 1992 ;Carrillo et al, 1993 ;Chesebro et al, 1991Chesebro et al, , 1992Hwang et al, 1991 ;Shoida et al, 1991 ;O'Brien et al, 1990), while the ability to induce the formation of syncytia in the host cells could be influenced by regions of Env outside V3 (Groenink et al, 1992 ;Forte et al, 1994 ;Todd et al, 1995 ;Holm-Hansen et al, 1995 ;Cornelissen et al, 1995 ;Andeweg et al, 1993Andeweg et al, , 1995Sullivan et al, 1993). These observations suggested to us that chimera J, containing the HIV-1 HXB# V3 loop in the HIV-1 Ba-L env, might be able to replicate in T-cell lines with more restricted support for HIV-1 replication than Sup-T1 and PM-1.…”
Section: Resultsmentioning
confidence: 99%
“…Several investigators have also pointed out the correlation between the ability of different strains of HIV-1 to induce syncytia, and their ability to replicate in the T-cell lines used to assess syncytium formation (Fouchier et al, 1995 ;De Jong et al, 1992 ;Schuitemaker et al, 1991). In addition, there have been recent reports of involvement of the V2 region of gp120 in the determination of the syncytium-forming phenotype (Andeweg et al, 1993(Andeweg et al, , 1995Cornelissen et al, 1995 ;Sullivan et al, 1993), and some reports of V3 loop phenotype not correlating with SI\NSI phenotype (Forte et al, 1994 ;Todd et al, 1995 ;HolmHansen et al, 1995 ;Cornelissen et al, 1995). In this study, we have used cell lines that not only support syncytium formation, but which also support the replication of a wide variety of strains of HIV-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation